El exilio español en México a través de dos visiones periodísticas, El Excélsior y El Nacional 1936-1939 - León Corona, Gabriela (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
After winning the elections of April 12, 1931 in Spain a new political era that led to the government of the Second Republic began. Just two days after Mexican President Pascual Ortiz Rubio recognized the government of Nicetas of Alcalá Zamora through its Mexican minister in Madrid, Enrique Gonzalez. This recognition informed the Spanish government on 16 April 1931. A month later were elevated to the status of the respective embassies and legations in Madrid Mexico City . Starting a new way of bilateral relations between Mexico and Spain . In 1931 , with a difference of a few months , the Second Spanish Republic in Mexico in May and September, were represented for the first time in the League of Nations . Mexico had remained outside the SDN about being excluded when it was founded , officially joining the defense was led by Minister of State Spanish Alejandro Lerroux . Spain also promoted the candidacy of Mexico as a nonpermanent member of the Board of the Company. Bilateral relations between Mexico and Spain were not without conflict , and between 1931 and 1933 , they primarily involve the Spanish colony. The problems are mainly raised in Veracruz, as a result of the agrarian policy of Governor Adalberto Tejeda , legislation to farming severely affected Spanish interests in the area and encouraged supposedly hispanófobas attitudes. Ambassador Alvarez del Vayo obtained that the matter be reviewed by the Mexican government.

Tras ganar la contienda electoral del 12 de abril de 1931 en España se inició una nueva etapa política que dio lugar al gobierno de la Segunda República. Sólo dos días después el presidente mexicano Pascual Ortiz Rubio reconoció al gobierno de Niceto de Alcalá Zamora por medio de su ministro mexicano en Madrid, Enrique González. Este comunicó el reconocimiento al ejecutivo español el 16 de abril de 1931. Un mes más tarde fueron elevadas a la categoría de embajadas las respectivas legaciones en Madrid y la Ciudad de México. Dando inicio a una nueva forma de las relaciones bilaterales entre México y España. En 1931, con una diferencia de pocos meses, la Segunda República Española en mayo y México en septiembre, se hicieron representar por primera vez en la Sociedad de Naciones. México se había mantenido al margen de la SDN por haber sido excluido cuando fue fundada, su ingreso oficialmente fue llevado por la defensa del ministro de Estado español Alejandro Lerroux. Asimismo, España promovió la candidatura de México como miembro no permanente del Consejo de la Sociedad. Las relaciones bilaterales entre México y España no estuvieron exentas de conflictos, y entre 1931 y 1933, éstos involucraron principalmente a la colonia española. Los problemas se suscitaron principalmente en Veracruz, como consecuencia de la política agrarista del gobernador Adalberto Tejeda, su legislación en materia agraria afectaba severamente los intereses españoles en la zona y alentaba supuestamente, actitudes hispanófobas. El embajador Álvarez del Vayo logró que el asunto fuera revisado por el gobierno mexicano.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2013-1217; Opción en historia de México; Exilio español; El Excélsior; El Nacional; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2425